An Impact of Business Cycles on Revenues and Expenditures of Communes in Poland - Marcin Łuszczyk; Agnieszka Janeta (Barometr Regionalny, 2019)
One of the basic functions of the state is mitigation of fluctuations in the business cycle. Increased activity in the period of economic slowdown should be demonstrated both by the state budget and local government units. However, the effectiveness of state intervention depends on the condition of the public finance sector. Therefore, in conditions of economic recovery, the state not only should balance its budget, but also should try to pay off at least part of the previously incurred liabilities. According to the authors, the permanent lack of financial discipline of the state, in the near future, will contribute to the budgetary imbalance of communes and will cause serious disruptions in the functioning of local self-governments.